Renovation of Modernist Architecture Study Based on Selected Cases - Joanna Jablonska; Lukasz Wojciechowski (Buildings, 2022)
Modernist architecture is one of the most significant movements which serve as grounds for contemporary creations. At the beginning of the 20th century, the impact of new structural and building technologies allowed designers to find new ways of architectural expression. It is rooted in thought-out composition and simplicity which serve as a background for the exposition of structure. The geometrical interplay of a building’s elements highlights the impressively thin structures and raw surfaces of novel building materials. Nowadays, in selected regions, the architecture of the Modernist Period is neglected or loosely refurbished. As an effect of this phenomenon, buildings are demolished or deprived of aesthetical values. Thus, this article aims at showing an overview of sectional research on good practice. We base the study of on-site design implementations of several modernist architecture refurbishments and focus on technology and design assumptions with optimised thermal modernisation. The paper reveals a set of examples for the refurbishment of modernist architecture, with calculations of heat energy coefficients of the initial and design phase. The presented thermal modernisations aim at adjusting buildings to new requirements concerning energy without any loss of initial architectural expression.